2009
DOI: 10.1111/j.1365-294x.2009.04460.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genomic methylation patterns during the formation of triploid asexual dandelion lineages

Abstract: DNA methylation is an epigenetic mechanism that has the potential to affect plant phenotypes and that is responsive to environmental and genomic stresses such as hybridization and polyploidization. We explored de novo methylation variation that arises during the formation of triploid asexual dandelions from diploid sexual mother plants using methylation-sensitive amplified fragment length polymorphism (MS-AFLP) analysis. In dandelions, triploid apomictic asexuals are produced from diploid sexual mothers that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 65 publications
5
92
0
1
Order By: Relevance
“…However, DNA methylation has been posited as a mechanism of phenotypic plasticity as well as a marker of stress response, and a number of studies have found a relationship between epigenetic variation and environment in support of this hypothesis (Herman & Sultan, 2016; Jablonka & Raz, 2009; Verhoeven, Jansen, et al., 2010; Verhoeven, Van Dijk, et al. 2010). Environmental stressors can induce variation in DNA methylation and in some cases, these environmentally induced methylation patterns can be inherited (Herrera & Bazaga, 2010, 2011; Verhoeven, Jansen, et al., 2010; Verhoeven, Van Dijk, et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, DNA methylation has been posited as a mechanism of phenotypic plasticity as well as a marker of stress response, and a number of studies have found a relationship between epigenetic variation and environment in support of this hypothesis (Herman & Sultan, 2016; Jablonka & Raz, 2009; Verhoeven, Jansen, et al., 2010; Verhoeven, Van Dijk, et al. 2010). Environmental stressors can induce variation in DNA methylation and in some cases, these environmentally induced methylation patterns can be inherited (Herrera & Bazaga, 2010, 2011; Verhoeven, Jansen, et al., 2010; Verhoeven, Van Dijk, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental stressors can induce variation in DNA methylation and in some cases, these environmentally induced methylation patterns can be inherited (Herrera & Bazaga, 2010, 2011; Verhoeven, Jansen, et al., 2010; Verhoeven, Van Dijk, et al. 2010), suggesting the potential for a signature of environmental response that is partially distinct from genetic variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, such regions may regulate gene activ− ity or transcriptional silencing (Finnegan 2001(Finnegan , 2010. DNA methylation can be in− herited influencing various plant traits (Henderson and Jacobsen 2007;Jablonka 2009;Verhoeven et al 2010). It may also provide some features allowing to survive in novel environments (Lira−Medeiros et al 2010).…”
Section: Introductionmentioning
confidence: 99%